2022
DOI: 10.1177/09730052221077846
|View full text |Cite
|
Sign up to set email alerts
|

Financial Leverage and Financial Performance of Savings and Credit Co-operative Societiesin Tanzania

Abstract: The purpose of this study is to examine the relationship between financial leverage and financial performance of Savings and Credit Cooperative Societies in Tanzania (SACCOS). The study used a panel data set of 115 SACCOS in Tanzania in the period 2011–14 and fixed-effects models for analysis. The study considered the direct relationship between financial leverage and financial performance and the moderating effect of board meetings on the relationship between financial leverage and the SACCOS’s financial perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…CEO duality p < 97 des not significant impact on firm performance. these findings are consistent with several prior studies [59]. Elsayed (2007) finds that CEO duality has no impact on corporate performance, measured as ROA and Tobin's Q, for a sample of publicly listed firms in Egypt from 2000 to 2004.…”
Section: Corporate Governance Financial Leverage Impact On Firm Perfo...supporting
confidence: 91%
See 2 more Smart Citations
“…CEO duality p < 97 des not significant impact on firm performance. these findings are consistent with several prior studies [59]. Elsayed (2007) finds that CEO duality has no impact on corporate performance, measured as ROA and Tobin's Q, for a sample of publicly listed firms in Egypt from 2000 to 2004.…”
Section: Corporate Governance Financial Leverage Impact On Firm Perfo...supporting
confidence: 91%
“…ROA profitability return on assets p < 0.03, INDR industry return p < 0.09, F. SIZE firm size p < 0.07, F.AGE firm age p < 0.03, EXPCAP capital investment p < 0.06, C.R current ratio p < 0.03, MKT market to book value p < 0.06, are positively associated with financial leverage NCF cash flow to total assets p < 0.03, FXR fixed assets ratio p < 0.07 negatively associated with firm performance. Financial leverage coefficient and p < 0.06 negatively associated with firm performance [59]. This finding supports our hypothesis that there is positive relationship between financial leverage and firm performance.…”
Section: Corporate Governance Financial Leverage Impact On Firm Perfo...supporting
confidence: 87%
See 1 more Smart Citation
“…It measures the ability of the SACCOS to provide loans using the deposits and meet members' withdrawal requirements at the same time. The capital to asset ratio (CAR) is computed as members' equity to total assets (Towo, 2022). In this study, members' equity included members' share capital, reserves, and retained earnings.…”
Section: Methodsmentioning
confidence: 99%
“…According to research conducted in Tanzania, capital structure has a significant and negative correlation with a company's performance [62]. A study on Nigerian oil companies found a negative correlation between capital structure and performance, as measured by return on equity (ROE), and it recommended increasing debt financing to protect shareholders' stakes in the companies [63].…”
Section: Capital Structure and Company Performancementioning
confidence: 99%